Implementation of dust control system using management and planning tools (MPT) - Mohd Zaki Al Hafiz bin Rosli, Mohd Zaki Al Hafiz (2008)
This report basically discusses the progress research done and basic understanding of the chosen topic, which is Multitask Anti-Dust Cleaner. The objective of this project is to introduce a new method in cleaning the SMT facilities especially in electronic production line.